Inside the “Black Box” of Sell‐Side Financial Analysts - BROWN, LAWRENCE D.; CALL, ANDREW C.; CLEMENT, MICHAEL B.; SHARP, NATHAN Y. (Journal of Accounting Research, 2015)
ABSTRACT Our objective is to penetrate the “black box” of sell‐side financial analysts by providing new insights into the inputs analysts use and the incentives they face. We survey 365 analysts and conduct 18 follow‐up interviews covering a wide range of topics, including the inputs to analysts’ earnings forecasts and stock recommendations, the value of their industry knowledge, the determinants of their compensation, the career benefits of Institutional Investor All‐Star status, and the factors they consider indicative of high‐quality earnings. One important finding is that private communication with management is a more useful input to analysts’ earnings forecasts and stock recommendations than their own primary research, recent earnings performance, and recent 10‐K and 10‐Q reports. Another notable finding is that issuing earnings forecasts and stock recommendations that are well below the consensus often leads to an increase in analysts’ credibility with their investing clients. We conduct cross‐sectional analyses that highlight the impact of analyst and brokerage characteristics on analysts’ inputs and incentives. Our findings are relevant to investors, managers, analysts, and academic researchers.